Analisis perilaku pencarian informasi Perguruan Tinggi Islam Malang dalam memenuhi tugas mata kuliah keagamaan - Nita Siti Mudawamah; Ferika Sandra (UIN Maulana Malik Ibrahim Malang, 2022)
Differences in students' religious educational backgrounds impact information-seeking behavior in completing assignments in the religious subjects they are taking. This study aims to analyze students' information-seeking behavior in Islamic tertiary institutions in Malang. This research uses descriptive quantitative methods because this research will describe the conditions that occur based on the information-seeking behavior experienced by students at that time. The number of students who became the sample of respondents in this study amounted to 60 active students, who were determined by random sampling technique. The results of this study indicate that the information-seeking behavior of Malang Islamic tertiary institutions in fulfilling religious subject assignments follows the stages of the Davi Ellis Model. The average index score shows that 59.98% of respondents often use the starting and chaining stages. At the browsing stage, the average index score obtained was 65.68%, indicating that respondents often carried out the browsing stage indicators. Likewise, the average index score obtained at the differentiating stage was 61.37%. The monitoring stage received an average index score of 75.83%. This score indicates that respondents continuously monitor the latest information when searching for religious information from various sources. The average index score for the extracting stage is 81.04%, which indicates that respondents are always selective in choosing relevant sources. The seventh stage is verifying, with an average score of 80.64%. This means that respondents always check the accuracy of the data that has been collected and selected. At the ending stage the average index score obtained at the ending stage was 84.17%. This means that respondents always determine the source of information obtained to be used when they succeed in finding information in completing religious tasks.